Advances of Hydrogel-Based Bioprinting for Cartilage Tissue Engineering - Han, Xue; Chang, Shuai; Zhang, Mingming; Bian, Xiangbing; Li, Chunlin; Li, Dawei (Frontiers in Bioengineering and Biotechnology, 2021)
Bioprinting has gained immense attention and achieved the revolutionized progress for application in the multifunctional tissue regeneration. On account of the precise structural fabrication and mimicking complexity, hydrogel-based bio-inks are widely adopted for cartilage tissue engineering. Although more and more researchers have reported a number of literatures in this field, many challenges that should be addressed for the development of three-dimensional (3D) bioprinting constructs still exist. Herein, this review is mainly focused on the introduction of various natural polymers and synthetic polymers in hydrogel-based bioprinted scaffolds, which are systematically discussed via emphasizing on the fabrication condition, mechanical property, biocompatibility, biodegradability, and biological performance for cartilage tissue repair. Further, this review describes the opportunities and challenges of this 3D bioprinting technique to construct complex bio-inks with adjustable mechanical and biological integrity, and meanwhile, the current possible solutions are also conducted for providing some suggestive ideas on developing more advanced bioprinting products from the bench to the clinic.